2006
DOI: 10.1111/j.1600-0501.2006.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteotome sinus floor elevation without grafting material: a 1‐year prospective pilot study with ITI implants

Abstract: Elevation of the sinus membrane alone without addition of bone grafting material can lead to bone formation beyond the original limits of the sinus floor. Despite a limited RBH at implant placement, a healing period of 3 months was sufficient to resist a torque of 35 N cm and to lead to a predictable implant function at the 1-year control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
148
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(169 citation statements)
references
References 33 publications
17
148
1
3
Order By: Relevance
“…2 In the crestal approach to graft-free sinus floor elevation, simultaneous implantation is needed, and the tips of the implants maintain the membrane at an adequate height by functioning essentially as "tent pegs." [3][4][5] In such a closed cavity below a lifted sinus membrane, the osteogenic potential of the bone and sinus membrane is highly protected. This method is considered less invasive and more affordable.…”
mentioning
confidence: 99%
“…2 In the crestal approach to graft-free sinus floor elevation, simultaneous implantation is needed, and the tips of the implants maintain the membrane at an adequate height by functioning essentially as "tent pegs." [3][4][5] In such a closed cavity below a lifted sinus membrane, the osteogenic potential of the bone and sinus membrane is highly protected. This method is considered less invasive and more affordable.…”
mentioning
confidence: 99%
“…This technique has been used as an alternative to conventional procedures [50][51][52][53][54][55][56][57][58][59][60][61][62][63]. MIAMBE balloon-harboring device (MiambeLTD, Netanya, Israel) consists of a stainless steel tube, three mm in diameter, that connects on its proximal end to the dedicated inflation syringe, and its distal portion has an embedded single use silicone balloon.…”
Section: Balloon Elevation Technique: Minimally Invasivementioning
confidence: 99%
“…To elevate the sinus floor indirectly and provide a buffering effect to sinus floor, bone graft material is added using an amalgam carrier. (Fig.6D)The sinus floor is elevated by repeated bone grafting and osteotome insertion followed by placement of implants (Fig.6E) [62]. In another study, Ostetomes can be used for SFE without bone grafting if residual bone height (RBH) is 5.4 mm and this could lead to a mean endo-sinus bone gain of 1.2-2.5 mm [63].…”
Section: Osteotome Technique (Ostsfe)mentioning
confidence: 99%
“…[15][16][17] However some studies reported new bone formation in animal and human's sinus with membrane elevation alone, resorbable gelatin sponge alone, venous blood alone and autologous fibrin gel with concentrated growth factors alone as alternatives to bone materials. [18][19][20][21][22][23][24][25] According to these studies, bone substitutes may not be a prerequisite for sinus augmentation. The function of elevated sinus membrane is controversial, but some studies reported that sinus membrane acted as periosteum and showed osteoinductive potetnial.…”
Section: Sinus Augmentation Using Lateral Window Approachmentioning
confidence: 99%